STABILITAS DAN PREDIKTABILITAS BETA SAHAM: STUDI EMPIRIS DI BURSA EFEK JAKARTA - Eduardus Tandelilin; I Wayan Nuka Lantara (Journal of Indonesian Economy and Business (JIEB), 2001)
The purpose of this research is to empirically analyze the stability and predictability of beta of common stocks in the Jakarta Stock Exchange (JSX). This is accomplished by first correcting the bias of beta using four-lead and four-lag versions of the Fowler and Rorke method. This study used the weekly returns of 95 stocks traded in the JSX from the first week of January 1994 to the last week of December 1996. The weekly Composite Index of the JSX was used as the proxy for market return. The stability and predictability of beta were studied over three 52-week periods by using the matrix transition test and correlation test. The result indicates that there is stability and predictability of common stocks during this research period. There is also an indication that portfolio betas are more stable and predictable than individual betas.